2021
DOI: 10.3390/cancers13215496
|View full text |Cite
|
Sign up to set email alerts
|

3D-Printed Replica and Porcine Explants for Pre-Clinical Optimization of Endoscopic Tumor Treatment by Magnetic Targeting

Abstract: Background: Animal models have limitations in cancer research, especially regarding anatomy-specific questions. An example is the exact endoscopic placement of magnetic field traps for the targeting of therapeutic nanoparticles. Three-dimensional-printed human replicas may be used to overcome these pitfalls. Methods: We developed a transparent method to fabricate a patient-specific replica, allowing for a broad scope of application. As an example, we then additively manufactured the relevant organs of a patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…This is because the tumor cells in 3D tumor model aggregated in clusters to form tumor spheres thereby reducing its sensitivity to drugs and increasing drug resistance. It has been shown that in 2D culture, only a planar structure existed without kinetic factors, while MDA-MB-231 cells were cultured in 2D monolayer flat, where the cells on the surface could be directly exposed to the drug and thus could directly influence the cell state [75,76].…”
Section: Cytotoxicity Test Of Curnps In 3d Tumor Model/environmentmentioning
confidence: 99%
“…This is because the tumor cells in 3D tumor model aggregated in clusters to form tumor spheres thereby reducing its sensitivity to drugs and increasing drug resistance. It has been shown that in 2D culture, only a planar structure existed without kinetic factors, while MDA-MB-231 cells were cultured in 2D monolayer flat, where the cells on the surface could be directly exposed to the drug and thus could directly influence the cell state [75,76].…”
Section: Cytotoxicity Test Of Curnps In 3d Tumor Model/environmentmentioning
confidence: 99%
“…Animal models deliver the necessary tissue function but also have limitations (i.e., the comparatively small number of specimens that can be investigated and high variability in the experimental conditions, e.g., due to biodynamic signatures) [14]. In addition, it is recommended to avoid animal experiments whenever possible [15]; however, reliable alternatives exist only for macroscopic structures [16] that do not mimic human tissue function. In tissue engineering, 3D models of vascular networks are already used for the design of scaffolds [17].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, computer-aided surgery (CAS) in the field of oral and maxillofacial treatment and the virtual planning of craniofacial surgical procedures are becoming increasingly popular [ 1 , 2 , 3 ]. Individualized 3D-printed templates and models, as an important computer-assisted surgery technology, is often applied for preoperative simulation, osteotomy, and occlusal reconstruction [ 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%